PERENCANAAN EMBUNG CABEAN DI KABUPATEN SUKOHARJO - Himawan, Edo; Kusumo N., Muhammad Donny; Sriyana, Sriyana; Sugiyanto, Sugiyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The construction of small dams Cabean is an effort in order to meet the water needs of the textile industry in Nguter Subdistrict, Sukoharjo Regency. The first step to design Cabean Small Dam is hidrology analysis such as: dependable discharge and water requirement. The dam is projected to supply water requirement in one subdistricts, water requirement for irrigation which has 50 ha of areas. Dependable discharge is discharge mainstay 80% fulfilled. Flood discharge plan of The Cabean Small Dam is calculated from rainfall data and the result of flow is 393.86 m3/s which taken from HSS Gamma 1 with PMF. Cabean Small Dam is designed with rock fill dam type. The height of the dam is 18 meters with slope ratio 1:2.25 at the upper course and 1:1.75 at the lower course. For 25 years lifetime and storage capacity 113,625 m3. The spillway design is choosen with 30 m wide and with stilling basin (USBR Type IV) which use 30 m of wide and 15 m of length as the dimension. The diversion tunnel design takes 150 m of length and 5 m of diameter. The cost of Cabean Small Dam Project is about Rp 21,343,482,440.00 (Twenty One Billion Thirty Hundred Fourty Three Million Four Hundred Eighty Two Thousand Four Hundred Fourty Rupiahs) with 48 weeks as time target of this project.